LA FILOSOFÍA ANGLOSAJONA - Hanna, Sonia Lópes (Prometeica - Revista de Filosofía y Ciencias, 2013)
MEYER, Michel [director]. La filosofía anglosajona,Primera edición, Buenos Aires, Prometeo Libros, 2010,564 pp. ISBN978-987-574-287-1Por Sonia López Hanna - UNMdP – CONICET